Em ondas com o turismo : o olhar na comunidade sobre o turismo do Farol de Santa Marta - Silva, Renan de Lima da (My University, 2016)
This dissertation is about tourism in Farol Beaches, viewed from the community look on the relations established in the activity. Aims to characterize the tourist practices on the Farol beaches; describe the relations between tourists and the community; and observe and discuss the possible consequences of these relationships in the locality tourism. This is an interdisciplinary study involving the areas Tourism, Hospitality, Communication and Anthropology. The methodological guidance is qualitative, exploratory, with the development of a literature review, participant observation with notebook and field diary and open interviews recorded and transcribed. In terms of results, there is an overview of the deterritorialization in the research, thought from the Baptist (2013), tourism as cultural expression, understood from Geertz (1989), characteristic of tourist practices of the Farol Beaches, dividing seasonally, according to Arantes and Santos (2010), the area with fishing and permeated by characteristics of the surf lifestyle. All these aspects have been demonstrated from the description of tourism and hospitality, according to the community look, fears and aspirations with those practices. The survey also, the developments of the relations established in tourist practices, with the marks the fact that the 'localism' surf and hospitality based on exchanges of Marcel Mauss (2002) are factors that help in preserving this culture, if we think from Castrogiovanni (2003), Barretto (2003) and Krippendorf (2000).
A presente dissertação é sobre o turismo nas Praias do Farol, analisado a partir do olhar da comunidade, sobre as relações estabelecidas na atividade. Tem como objetivos caracterizar as práticas turísticas nas Praias do Farol; descrever as relações estabelecidas entre os turistas e a comunidade; e observar e discutir os eventuais desdobramentos dessas relações e o turismo da localidade. Trata-se de um estudo transdisciplinar, envolvendo as áreas Turismo, Hospitalidade, Comunicação e Antropologia. A orientação metodológica é qualitativa, de cunho exploratório, com o desenvolvimento de revisão bibliográfica, observação participante com caderno e diário de campo e entrevistas abertas gravadas e transcritas. Em termos de resultados, tem-se um panorama sobre as desterritoralizações da pesquisa, pensadas a partir de Baptista (2013); o turismo como manifestação cultural, entendido a partir de Geertz (1989); a característica das práticas turísticas das Praias do Farol, dividindo sazonalmente, segundo Arantes e Santos (2010); o espaço com a pesca e perpassado por características do estilo de vida do surf. Todos esses aspectos foram demonstrados a partir da descrição do turismo e da hospitalidade, segundo o olhar da comunidade, seus medos e pretensões com essas práticas. São apresentados, ainda, os desdobramentos das relações estabelecidas nas práticas turísticas, tendo como marca o fato de que o ‘localismo’ do surfe e a hospitalidade baseada nas trocas de Marcel Mauss (2002) são fatores que ajudam na preservação dessa cultura, se pensarmos a partir de Castrogiovanni (2003), Barretto (2003) e Krippendorf (2000).
Keywords: Turismo - Santa Catarina; Turismo - Aspectos sociais; Hospitalidade; Recursos naturais; Praias; Tourist trade - Santa Catarina (Brazil); Tourist trade - Social aspects; Hospitality; Natural resources; Beaches